An Astronomical Attempt to Determine the Temporal Origin of an Episode of the Armenian Epic "SasnayTsrer" - Broutian, G.
An attempt was made to estimate the time period of the Armenian epic "Sasnay Tsrer" by astronomical means. An episode in which Tsovinar mentions a bright star as night guide for sending her sons from Mesopotamia to Armenia has been examined from the point of view of astronomy. On basis of the "khachapasht" (cross worshipers) self-proclamation of representatives of the House of Sasun and wearing the sign of the cross on their right hand, this guiding star is identified with the constellation Cygnus (ancient Armenian Angkh - Vulture), which depicts the outline of a cross in the northern sky. Subsequently, we calculated when Cygnus' main star, Deneb, was closest to the North Pole. The calculations show that this event took place 17,500 years ago. This time frame was taken as the time of the creation of the above-mentioned episode of the Sasnay Tsrer Epic.
Keywords: Astronomy; Literature